Fracture Resistance and Stress Distribution of Polyether Ether Ketone as Post-Core In Endodontically Treated Tooth: A Systematic Review : Fracture Resistance and Stress Distribution of Polyether Ether Ketone - Puteri Ridha Ramadhani; Wandania Farahanny; Trimurni Abidin; Dennis Dennis (Journal of Syiah Kuala Dentistry Society, 2025)
Various post and core materials have been developed for endodontic restorations. Polyether ether ketone (PEEK) has an elastic modulus similar to dentin, reducing stress and improving tooth biomechanics, which may lower the risk of complications in final restorations. The objective of this systematic review was to synthesize findings from studies comparing the fracture resistance and stress distribution of post and core systems made from polyether ether ketone (PEEK) with those constructed from conventional materials. The review, conducted following PRISMA 2020 guidelines, involved a search of multiple databases, including PubMed, ScienceDirect, Wiley Online Library, Semantic Scholar, and Google Scholar, for studies published between 2014 and 2024. Keywords such as polyether ether ketone, PEEK, post-core, and endodontically treated teeth were used, resulting in 788 articles, of which 13 met the eligibility criteria. The findings indicated that PEEK post and core systems exhibited lower stress concentrations compared to conventional materials, thereby reducing the risk of irreparable root fractures. PEEK shows great potential as a material for post and core restorations. However, its use in endodontically treated teeth is not well-explored, and further research is required to better understand its mechanical properties in this context.